2017
DOI: 10.1371/journal.ppat.1006370
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylated STAT5 directly facilitates parvovirus B19 DNA replication in human erythroid progenitors through interaction with the MCM complex

Abstract: Productive infection of human parvovirus B19 (B19V) exhibits high tropism for burst forming unit erythroid (BFU-E) and colony forming unit erythroid (CFU-E) progenitor cells in human bone marrow and fetal liver. This exclusive restriction of the virus replication to human erythroid progenitor cells is partly due to the intracellular factors that are essential for viral DNA replication, including erythropoietin signaling. Efficient B19V replication also requires hypoxic conditions, which upregulate the signal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 77 publications
1
45
0
Order By: Relevance
“…Gel shift assays have shown NS1 binding to AGGGCGGA octanucleotide GC elements upstream of the P6 promoter (Gareus et al, 1998; Raab et al, 2001; Raab et al, 2002). Additionally, within the B19V ITR, NS1 binding motifs have been identified as GC rich imperfect palindromic repeats of CCGGCGGC (Ganaie et al, 2017; Guan et al, 2009; Sanchez et al, 2016). Recent studies have found NS1 can complex with STAT5 to facilitate replication (Ganaie et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gel shift assays have shown NS1 binding to AGGGCGGA octanucleotide GC elements upstream of the P6 promoter (Gareus et al, 1998; Raab et al, 2001; Raab et al, 2002). Additionally, within the B19V ITR, NS1 binding motifs have been identified as GC rich imperfect palindromic repeats of CCGGCGGC (Ganaie et al, 2017; Guan et al, 2009; Sanchez et al, 2016). Recent studies have found NS1 can complex with STAT5 to facilitate replication (Ganaie et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, within the B19V ITR, NS1 binding motifs have been identified as GC rich imperfect palindromic repeats of CCGGCGGC (Ganaie et al, 2017; Guan et al, 2009; Sanchez et al, 2016). Recent studies have found NS1 can complex with STAT5 to facilitate replication (Ganaie et al, 2017). This genomic configuration of NS1 interacting with DNA and cellular factors is similar to that of AAV Rep binding domains (McCarty et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein expression was induced by addition of IPTG (isopropyl-␤-Dthiogalactopyranoside) to the bacterial culture at 1 mM. Protein was purified with Ni-nitrilotriacetic acid (NTA) affinity agarose (Qiagen) as described previously (42).…”
Section: Methodsmentioning
confidence: 99%
“…The minimal replication origin (Ori) of B19V DNA has been identified to be 67 nucleotides (nt), which includes a STAT5-binding element (STAT5BE), a trs or nicking site, two copies of the NS1-binding element (NS1BE), and the putative cellular factorbinding site (CFBE) ( Fig. 2A) (25,27,41,42). Specific cleavage of the ssDNA Ori has been demonstrated in an in vitro nicking assay using the purified B19V NS1 N terminus (aa 1 to 176) and a 5=-end 32 P-labeled oligonucleotide that contain the trs (28).…”
mentioning
confidence: 99%